2020
DOI: 10.21203/rs.3.rs-35418/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A survey of psychological responses during the Coronavirus Disease 2019 (COVID-19) epidemic among Chinese police officers in Wuhu

Abstract: Background The outbreak of Coronavirus Disease 2019 (COVID-19) has caused serious threats to people’s health and lives. The police officers are bravely fighting on the front lines of the epidemic. Our study is the first survey of psychological response in the police officers of China during the tumultuous time of the COVID − 19 outbreak. Methods A cross-sectional online questionnaire was conducted to the police officers from 5 districts (Yijiang, Sanshan, Jiujiang, jinghu and Jingkai) and 4 counties (Wuhu, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…In the Chinese study, 12.17% of the police personnel had moderate to severe depression and 8.79% had moderate to evere anxiety. 12 In comparison to our study, police personnel in the Chinese study had comparatively low depression and anxiety.…”
Section: Discussioncontrasting
confidence: 74%
“…In the Chinese study, 12.17% of the police personnel had moderate to severe depression and 8.79% had moderate to evere anxiety. 12 In comparison to our study, police personnel in the Chinese study had comparatively low depression and anxiety.…”
Section: Discussioncontrasting
confidence: 74%
“…These problems included 14.6% depression, 14.2% PTSD, 25% at a high risk of drinking above the recommended levels of alcohol and 9.6% experiencing generalised anxiety. A study of police officers in China engaged in responding to COVID-19 found 12% had moderate or high depression and 9% had moderate-to-high anxiety (Yuan et al, 2020).…”
Section: Trauma Signs Symptoms and Resilience In Policingmentioning
confidence: 99%
“…It is therefore imperative to examine the antecedents of police stress during health crises. Although recent studies have discussed the effects of COVID-19 on police mental health (Drew and Martin, 2020;Jennings and Perez, 2020;Stogner et al, 2020), only two have empirically investigated police stress (Yuan et al, 2020;Frenkel et al, 2021), leaving many questions unanswered.…”
Section: Introductionmentioning
confidence: 99%